Risk of Depression, Chronic Morbidities, and l-Thyroxine Treatment in Hashimoto Thyroiditis in Taiwan: A Nationwide Cohort Study. Issue 6 (February 2016) - Lin, I-Ching; Chen, Hsin-Hung; Yeh, Su-Yin; Lin, Cheng-Li; Kao, Chia-Hung
Abstract : Abstract: The aim of this study was to evaluate the risk of depression in and effect of L-thyroxine therapy on patients with Hashimoto thyroiditis (HT) in Taiwan. In this retrospective, nationwide cohort study, we retrieved data from the Longitudinal Health Insurance Database 2000. We collected data of 1220 patients with HT and 4880 patients without HT for the period 2000 to 2011. The mean follow-up period for the HT cohort was 5.77 years. Univariate and multivariate Cox proportional hazards regression models were used to estimate the risk of depression in the HT cohort. In the HT cohort, 89.6% of the patients were women. Compared with the non-HT cohort, the HT cohort exhibited a higher prevalence of diabetes mellitus, hyperlipidemia, and coronary artery disease. Furthermore, the HT cohort showed a higher overall incidence of depression compared with the non-HT cohort (8.67 and 5.49 per 1000 person-year; crude hazard ratio [HR] = 1.58, 95% confidence interval [CI] = 1.18–2.13). The risk of depression decreased after administration of L-thyroxine treatment for more than 1 year (adjusted HR = 1.02; 95% CI = 0.66–1.59). In Taiwan, the overall incidence of depression was greater in the young HT cohort. L-thyroxine treatment reduced the risk of depression.